1989
DOI: 10.1021/j100347a042
|View full text |Cite
|
Sign up to set email alerts
|

Acetone photophysics in seeded supersonic molecular beams

Abstract: be delocalized in the three oxygen atoms of N03" like the resonance structure 111, which may be less electrophilic and less reactive. In the condensed phase, N03' is reported to be a Yshaped structure,36 in which an unpaired electron is localized on one oxygen atom like the canonical structures I and II. This radical center is quite reactive and electrophilic. This change of the electronic distribution may also be one of the causes for the medium effect.For the reaction of N03* with phenol in the gas phase,37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 0 publications
7
41
0
Order By: Relevance
“…As discussed in Ref. 37, the gradual decrease of the rate is compatible with the theory briefly outlined above (cf. Eq.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…As discussed in Ref. 37, the gradual decrease of the rate is compatible with the theory briefly outlined above (cf. Eq.…”
Section: Methodssupporting
confidence: 88%
“…6-9.36 Here we quote the main features of the analysis, more details may be found in Ref. 37. Initial excitation is assumed to entail a single SI state, and NT1 states.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 illustrates the potential energy levels of the acetone molecule assembled from the available spectroscopic information. 5,8,11,[18][19][20] Only those states relevant to this study are shown. With the wavelengths employed in this study, the S 1 state can be accessed by one photon of 259 nm; two photons of 390 nm will access the 3s Rydberg state, while two photons of 259 nm or three photons of 390 nm can access the Rydberg states near the ionization continuum.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This transition has also been observed by threshold electron-impact spectroscopy by van Veen et al 43 However, the maximum could not be reported in that study because of the strong n→3s transition to the 1 1 B 2 Rydberg state near 6.35 eV, 7,10,40,41,43 which is in agreement with various theoretical predictions. 2,4,42 Interestingly in gas-phase photolysis studies, [13][14][15][16][17][18][19][20][21][22] the dissociation of acetone into two methyl radicals and a CO has been attributed to this Rydberg transition.…”
Section: A Electronic Energy Lossesmentioning
confidence: 99%
“…The electronic spectroscopy of acetone 2-10 is of further particular interest to increase our understanding of the mechanisms of photolysis, 11,12 especially regarding three-body dissociation dynamics. [13][14][15][16][17][18][19][20][21][22] Strong dissociation channels leading to the formation of various molecular fragments have been reported for many electronic states. In the study of the electronic spectrum of acetone, both experiment 5,6,23 and theoretical calculations 2 have revealed the existence of a coupling between some Rydberg states and the →* valence state of the molecule.…”
Section: Introductionmentioning
confidence: 99%